Analysis of lysine acetylation in tomato spot wilt virus infection in Nicotiana benthamiana - Gong, Yanwei; Li, Ying; Liu, Dongyang; Jiang, Lianqiang; Liang, Hui; Wu, Yuanhua; Wang, Fenglong; Yang, Jinguang (Frontiers in Microbiology, 2023)
Protein lysine acetylation (Kac) is a model for all acylation modification studies. Kac plays a critical role in eukaryotes and prokaryotes. It is mainly involved in six major biological functions: gene expression, signal transduction, cell development, protein conversion, metabolism, and metabolite transport. We investigated and compared the acetylation modification of proteins in healthy and tomato spot wilt virus (TSWV)-infected N.benthamiana leaves. We identified 3418 acetylated lysine sites on 1962 proteins based on the inclusion of quantitative information. After comparing the acetylation levels of proteins in the TSWV-infected and control groups, it was observed that 408 sites on 294 proteins were upregulated and 284 sites on 219 proteins (involved in pentose phosphate, photosynthesis, and carbon fixation in photosynthesis) were downregulated after the infection. Overall, 35 conserved motifs were extracted, of which K*R represented 1334 (31.63%) enrichment motifs and was the most common combination. Bioinformatic analysis revealed that most of the proteins with Kac sites were located in the chloroplast and cytoplasm. They were involved in biological processes, such as cellular and metabolic processes. In conclusion, our results revealed that Kac may participate in the regulation of TSWV infection in N. benthamiana.